Potential Cross-Border Double Taxation on Death Limits Global Investment Opportunities for Long Term South African Resident Investors - demonstrated through an analysis of the international tax consequences that arise for a South African resident who holds an investment in a portfolio of stock listed in the United States of America at the date of death - Wilson, Kirsty (Department of Finance and Tax, 2020)
This dissertation examines the impact of the imposition of both estate duty and capital gains tax (CGT) by South Africa (SA) on South African resident investors at the date of death.1 The focus of this dissertation, within this chosen area of study, is the effect of the imposition of these two taxes on cross-border transactions; this study examines the international tax consequences that arise on death, should a SA resident investor hold foreign situs assets at such time. The study uses a portfolio of stock listed in the United States of America (US) to demonstrate that the imposition of both estate duty and CGT by SA at the date of death may result in unresolved double taxation or at the very least the imposition of taxes that are confiscatory, excessive or prejudicial to SA resident investors. In order to demonstrate that double taxation may exist or that confiscatory, excessive and prejudicial taxes may arise, the study outlines the current legislation in SA and the US, as well as the relevant unilateral and bilateral relief available to such an investor. The study then goes on to determine the global tax liability that would result for the investor in question at the date of death. After determining the global tax liability, the study analyses whether the relief available to the investor is sufficient in preventing double taxation or taxes that may be considered prejudicial, confiscatory and/or excessive. Where it is found that double taxation persists or prejudicial, excessive and confiscatory taxes exists, the study recommends action that should be taken by the relevant authorities to remedy such concerns.